The relationship between nutritional status based on nutritional risk index (NRI) and length of stay of digestive surgery patients - Kusuma, Dian Reginalda; Putra, Kadek Agus Heryana; Kurniyanta, I Putu (DiscoverSys Inc., 2019)
ABSTRACTBackground: Malnutrition is a common concomitant illness that can be found in digestive surgery patients.The risk of malnutrition in digestive surgery patients is often overlooked even though malnutrition has beenknown to be associated with poor postoperative outcomes. The study aimed to analyze the relationship of nutritional status based on the Nutritional Risk Index (NRI) and length of stay of digestive surgery patientsin Sanglah General Hospital. Patients and Methods: The design of this study is an analytical cross-sectional using secondary data fromthe medical record of the digestive surgery patients in Sanglah General Hospital. Data on body weight andserum albumin level were used to identify the preoperative nutritional status of the patients based on NRI. Results: Of the 42 patients involved in this study, 54.8% of patients have poor nutritional status and the remainder 45.2% of patients have good nutritional status. The result of the statistical analysis showed asignificant relationship between nutritional status and length of stay. The result of the logistic regressiontest showed that the prevalence of long hospitalizations (≥11 days) were 5.2 times greater in digestivesurgery patients with poor preoperative nutritional status compared to patients with good nutritionalstatus. Conclusion: This study shows that poor nutritional status is a significant problem for digestive surgery patients and it is one of the factors that contribute to a longer hospital stay.